Poverty and patterns of growth - Hasan, Rana.; Quibria, M. G. (Muhammad Ghulam); Asian Development Bank. Economics and Research Department (Manila : Asian Development Bank, 2002)
With reference to East Asia.
'August 2002'
Includes bibliographical references (p. 8-9).
Keywords: Poverty -- East Asia; East Asia -- Economic conditions